SIFAT TANAH DAN AIR YANG TERPENGARUH TSUNAMI DI KECAMATAN LHOKNGA KABUPATEN ACEH BESAR - Syakur Syakur; Hairul Basri; Sufardi Sufardi; Muhammad Hatta (Jurnal Floratek, 2012)
Lhoknga Sub District was one of regions experiencing earthquake and tsunami disaster occurred on 26 December 2004. The aims of the research were to evaluate soil characteristics, to study land suitability and to propose recommendation of land use and rehabilitation of the tsunami affected agricultural area in Lhoknga Sub District. The result showed that soil textures were varied from very coarse at the area near to the coastline to rather fine at the area far from the coast. The soil structures of topsoil was generally plate and blocky, while that of subsoil was generally massive. The quality of irrigation water in was still suitable for crops, the pH of water was neutral and low in salinity (0,4 mS cm-1). The water quality of wells was high (good) and water quality of drainage and surface water was low (rather bad). Water quality of wells was good enough, indicated by low water salinity (0,26-0,78 mS cm-1) and  low of SAR value. The recommendations for land reclamation were (1) cleaning and repairing of irrigation and drainage channel  (2) leaching of salinity in topsoil from soil profile by flooding method (basin irrigation) or furrow irrigation,  (3) constructing the ditches for cultivation in managing the excess of salinity, (4) establishing ditches for paddy, and (5) removing the sediment above the topsoil.